FOG AND RAIN ATTENUATION CHARACTERIZATION AND PERFORMANCE OF TERRESTRIAL FREE SPACE OPTICAL COMMUNICATION IN AKURE, NIGERIA - O, Ajewole M.; A, Owolawi P.; S, Ojo J.; M., Adetunji R. (APTIKOM Journal on Computer Science and Information Technologies, 2019)
Reliable broadband communication requires secure high data rate and bandwidth links. With the observedincrease in broadband users, known communication systems such as RF and microwave links cannot promise suchrequirements due to link interference and low bandwidth. A current communication system that promises suchrequirements and more is Free Space Optical (FSO) communication. This system basically involves the transmissionof signal-modulated optical radiation from a transmitter to a receiver through the atmosphere or outer space. However,location-variant atmospheric channel degrades the performance of an FSO system under severe atmosphericconditions, thus necessitating local atmospheric attenuation studies.This paper presents the characterization of both fog- and rain-induced attenuation and the performance ofan FSO system in a terrestrial terrain at Akure, Nigeria. One-year archived visibility data and in-situ measured 1-minute integration time rain rate data obtained from Nigerian Meteorological Agency (NIMET) and the Departmentof Physics, Federal University of Technology, Akure were used to compute the fog- and rain-induced specificattenuations using Kruse model and Carboneur model respectively. The performance of the FSO system is analyzedthrough link margin by using the parameters of a commercial optical transceiver, Terescope 5000.